Prognostic models for estimating severity of disease and predicting 30-day mortality of Hypervirulent Klebsiella pneumoniae infections: a bicentric retrospective study - Jieen Huang; Yanzhu Chen; Ming Li; Shujin Xie; Huasheng Tong; Zhusheng Guo; Yi Chen (BMC Infectious Diseases, 2023)
Abstract Background Hypervirulent Klebsiella pneumoniae (hvKP) is emerging globally and can cause various, severe infections in healthy individuals. However, the clinical manifestations of hvKP infections are nonspecific, and there is no gold standard for differentiating hvKP strains. Our objective was to develop prognostic models for estimating severity of disease and predicting 30-day all-cause mortality in patients with hvKP infections. Methods We enrolled 116 patients diagnosed with hvKP infections and obtained their demographic and clinical data. Taking septic shock and acute respiratory distress syndrome (ARDS) as the primary outcomes for disease severity and 30-day all-cause mortality as the primary outcome for clinical prognosis, we explored the influencing factors and constructed prognostic models. Results The results showed that increased Acute Physiologic and Chronic Health Evaluation (APACHE) II score [odds ratio (OR) = 1.146; 95% confidence interval (CI), 1.059–1.240], decreased albumin (ALB) level (OR = 0.867; 95% CI, 0.758–0.990), diabetes (OR = 9.591; 95% CI, 1.766–52.075) and high procalcitonin (PCT) level (OR = 1.051; 95%CI, 1.005–1.099) were independent risk factors for septic shock. And increased APACHE II score (OR = 1.254; 95% CI, 1.110–1.147), community-acquired pneumonia (CAP) (OR = 11.880; 95% CI, 2.524–55.923), and extrahepatic lesion involved (OR = 14.718; 95% CI, 1.005–215.502) were independent risk factors for ARDS. Prognostic models were constructed for disease severity with these independent risk factors, and the models were significantly correlated with continuous renal replacement therapy (CRRT) duration, vasopressor duration, mechanical ventilator duration and length of ICU stay. The 30-day all-cause mortality rate in our study was 28.4%. Younger age [hazard ratio (HR) = 0.947; 95% CI, 0.923–0.973)], increased APACHE II score (HR = 1.157; 95% CI, 1.110–1.207), and decreased ALB level (HR = 0.924; 95% CI, 0.869–0.983) were the independent risk factors for 30-day all-cause mortality. A prediction model for 30-day mortality was constructed, which had a good validation effect. Conclusions We developed validated models containing routine clinical parameters for estimating disease severity and predicting 30-day mortality in patients with hvKP infections and confirmed their calibration. The models may assist clinicians in assessing disease severity and estimating the 30-day mortality early.